Search for heavy particles decaying into electron-positron pairs in pp̄ collisions - Abazov, V; Abbott, B; Abdesselam, A; Abolins, M; Abramov, V; Acharya, B; Adams, D; Adams, M; Ahmed, SN; Alexeev, G; Alves, G; Amos, N; et al. (2001)
The data collected by DO detector was used to study the decay of heavy particles into electron-positron pairs during collisions. The dielectron invariant mass spectra for the events with both electrons in central region and with one electron in central region and other in forward region of central calorimeter (CC)/end calorimeter (EC) were also studied. PYTHIA was used to determine the product of cross section and branching ratio for the system. The superimposed histograms represented the estimated spectrum from standard model processes and instrumental effects.